The Roles of Long-Term Hyperhomocysteinemia and Micronutrient Supplementation in the AppNL–G–F Model of Alzheimer’s Disease - Nieraad, Hendrik; de Bruin, Natasja; Arne, Olga; Hofmann, Martine C. J.; Pannwitz, Nina; Resch, Eduard; Luckhardt, Sonja; Schneider, Ann-Kathrin; Trautmann, Sandra; Schreiber, Yannick; Gurke, Robert; Parnham, Michael J.; et al. (Frontiers in Aging Neuroscience, 2022)
A causal contribution of hyperhomocysteinemia to cognitive decline and Alzheimer’s disease (AD), as well as potential prevention or mitigation of the pathology by dietary intervention, have frequently been subjects of controversy. In the present in vivo study, we attempted to further elucidate the impact of elevated homocysteine (HCys) and homocysteic acid (HCA) levels, induced by dietary B-vitamin deficiency, and micronutrient supplementation on AD-like pathology, which was simulated using the amyloid-based AppNL-G-F knock-in mouse model. For this purpose, cognitive assessment was complemented by analyses of ex vivo parameters in whole blood, serum, CSF and brain tissues from the mice. Furthermore, neurotoxicity of HCys and HCA was as-sessed in a separate in vitro assay. In confirmation of our previous study, older AppNL-G-F mice also exhibited subtle phenotypic impairment and extensive cerebral amyloidosis, whereas dietary manipulations did not result in significant effects. As revealed by proximity extension assay-based proteome analysis, the AppNL-G-F genotype led to an upregulation of AD-characteristic neuronal markers. Hyperhomocysteinemia, in contrast, indicated mainly vascular effects. Overall, since there was an absence of a distinct phenotype despite both a significant amyloid-β burden and serum HCys elevation, the results in this study did not corroborate the pathological role of amyloid-β according to the “amyloid hypothesis”, nor of hyperhomocysteinemia on cognitive performance. Nevertheless, this study aided in further characterizing the AppNL-G-F model and in elucidating the role of HCys in diverse biological processes. The idea of AD prevention with the investigated micronutrients, however, was not supported, at least in this mouse model of the disease.